PENGARUH CONTENT MARKETING, ELECTRONIC WORD OF MOUTH (E-WOM) DAN PRICE AFFORDABILITY TERHADAP MINAT BELI KULINER PADA AKUN INSTAGRAM @MADIUNNGEMIL - Fatika Fakhrunnisa; Tatik Mulyati; Hartirini Warnaningtyas (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of content marketing, electronic word of mouth (e-WoM), and price affordability on culinary purchase interest through the Instagram account @madiunngemil, a social media platform focused on promoting and recommending local culinary businesses in Madiun City and its surrounding areas. The rapid development of digital marketing and the increasing use of social media have significantly influenced consumer behavior in seeking culinary information and recommendations. This research employed a quantitative approach using purposive sampling techniques. Data were collected through questionnaires distributed to students of Universitas Merdeka Madiun who actively use Instagram and have accessed the @madiunngemil account. The data were analyzed using multiple linear regression with the assistance of JASP software. The findings revealed that content marketing, e-WoM, and price affordability positively and significantly influence purchase interest both partially and simultaneously. Furthermore, content marketing was identified as the most dominant variable affecting purchase interest. These results suggest that attractive content, positive consumer reviews, and affordable pricing strategies can effectively increase consumers’ culinary purchase interest among students.